2008
DOI: 10.1590/s0102-05362008000200018
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of potato genotypes (Solanum spp.) to Bemisia tabaci biotype B

Abstract: The resistance of 24 potato genotypes to B. tabaci (Genn.) biotype B (Hemiptera: Aleyrodidae) was evaluated in five greenhouse experiments. The first experiment we evaluated the attractiveness and preference for oviposition in a free-choice test (randomized blocks, 24 treatments, and eight replications). In two other experiments we evaluated no-choice preference for oviposition (randomized blocks, six treatments, and ten replications). The whitefly egg-adult cycle was monitored using a statistical design in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
4
4
0
Order By: Relevance
“…This same relationship has been reported in other crop plants, such as potato (Silva et al. ), melon (Coelho et al. ) and beans (Oriani et al.…”
Section: Discussionsupporting
confidence: 84%
“…This same relationship has been reported in other crop plants, such as potato (Silva et al. ), melon (Coelho et al. ) and beans (Oriani et al.…”
Section: Discussionsupporting
confidence: 84%
“…A positive and significant correlation between the number of adults and eggs was observed in our trials, corroborating with other studies with tomato and soybean (Silva et al 2008, Valle et al 2012, Baldin et al 2017, and indicating that adult whiteflies prefer these surface for feeding and oviposition (Van Lenteren & Noldus 1990). In addition, there was also a negative correlation between trichomes and the number of adults and eggs, unlike studies conducted by other authors with common bean (Oriani et al 2005), which showed positive correlations between egg numbers and density of acicular (long) and unciform (short) trichomes.…”
Section: Principal Component Analysissupporting
confidence: 92%
“…Overall, our results suggest that ToCV manipulates the host phenotype on potato in ways that likely enhance its spread by B. tabaci MEAM1 in potato fields. However, it is unclear whether ToCV transmission by B. tabaci MEAM1 is enhanced to a greater extent in plantings of ‘Agata’, which is susceptible to both the whitefly and ToCV (Silva et al ., 2008; Freitas et al ., 2012) and therefore may serve as a better reservoir than the moderately whitefly-resistant Bach-4. On one hand, we did not find that infection by ToCV in ‘Agata’ increases the chances of virus acquisition by B. tabaci MEAM1, as the whiteflies did not discriminate ToCV-infected from mock-inoculated plants of ‘Agata’.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we investigated whether the behaviour and biology of B. tabaci MEAM1 increases the likelihood of ToCV acquisition, transmission and spread in potato. We selected two potato clones, one susceptible (‘Agata’) and the other moderately resistant (Bach-4) to B. tabaci MEAM1 (Silva et al ., 2008; Rocha et al ., 2012). We specifically tested the following hypotheses for both clones: ( i ) whiteflies orient preferentially to ToCV-infected potato clones compared with non-infected clones; ( ii ) whitefly females prefer to oviposit on ToCV-infected potato clones compared with non-infected clones; ( iii ) whiteflies feeding on the ToCV-infected clone migrate preferentially to the non-infected clone, optimizing the spread of the virus; ( iv ) the life cycle of whiteflies that have been fed on the ToCV-infected potato plants is shorter compared with individuals that have been fed on the non-infected plants; and ( v ) virus manipulation of the plant for enhancing transmission is more pronounced in the susceptible than in the moderately resistant clone, as proposed by Mauck (2016).…”
Section: Introductionmentioning
confidence: 99%